THE CONSTITUTION - THE GUARANTEE OF A FREE AND PROSPEROUS LIFE - Sulaymanova Zaima (Web of Journals Publishing, 2025)
This article discusses the adoption of the Constitution of the Republic of Uzbekistan, its refinement over the years, its historical significance, the enforcement of its provisions, and the enactment of laws and decisions based on it. Particular focus is given to the adoption of the new Constitution through a referendum and its entry into force.
Keywords: Uzbekistan, Constitution, Islam Karimov, Shavkat Mirziyoyev, Our Basic Law, our people, independence, human rights, President of the State.